What type of client do you need? The brand value co-creation in the banking sector - Peña-García, Nathalie; Losada-Otálora, Mauricio; Juliao-Rossi, Jorge (Frontiers in Psychology, 2022)
Service-dominant logic established that for the success of service industries, it is vital to acknowledge the customer as an active agent in the commercial ecosystem. To carry it out, the consumer must participate in value creation. The resource integration theory exposes the importance of recognizing the customer as an agent capable of improving the company’s competitive advantage. It is only necessary for the participants to perceive benefits to make their resources available and integrate them into the co-creation process. This study aims to find the key customer-based factors that influence the brand value co-creation (VCC) process in the banking sector, analyzing the dynamics in different customers across national cultures and idiosyncrasies. In this paper, we analyze the potential heterogeneous idiosyncrasy of customers and how it leads to becoming more engaged in the co-creation process. Quantitative research was performed in five countries, obtaining a total of 2,029 valid questionnaires where latent profile analyses and ANOVAs were performed to identify and describe the latent profiles (LPA) of consumer co-creators of brand value. Afterward, a PLS-SEM was performed to test the research model in each segment. The results show four different profiles of customer co-creators of brand value, from non-co-creators (detractors), skeptical and neutral, to customers committed to co-creating brand value with their banks. The results indicate that detractor customers lack the motivations and resources to carry out co-creation behaviors. On the other hand, creativity and connectedness were crucial for customers co-creators of value. To the authors’ understanding, no studies have used latent segmentation to find the profiles of customer co-creators of brand value.